Association Between Post-COVID Consequences and Cognitive Performance in University Students: A Cross-Sectional Study - Sergey Malykh; Valeriia Demareva; Victoria Ismatullina; Timofey Adamovich; Tamara Malykh; Tatiana Tikhomirova (European Journal of Investigation in Health, Psychology and Education, 2026)
Post-COVID symptoms frequently include cognitive complaints, yet evidence on objectively measured cognitive performance in large samples of young adults remains limited. This study examined associations between self-reported post-COVID consequences and objective cognitive performance in university students, with particular attention to acute COVID-19 severity. The sample comprised 7482 students aged 17–23 years: 3945 reported no previous COVID-19, 1676 reported previous COVID-19 without post-COVID consequences, and 1861 reported previous COVID-19 with post-COVID consequences. Visuospatial working memory was assessed using the Corsi Block Tapping Test (CTB), and choice-response performance was assessed using accuracy and mean correct-response latency in a four-choice reaction time task. Analyses accounted for age, sex, and clustering by university; among previously infected participants, models additionally adjusted for perceived acute COVID-19 severity. The primary adjusted analyses included 7117 participants for CTB and 6361 participants for the cleaned choice-response accuracy and latency analyses. In the three-group analysis, students reporting post-COVID consequences had slightly lower CTB scores than those without previous COVID-19 (B = −0.146, 95% CI [−0.277, −0.015], p = 0.029), although the effect was small and was not fully robust in an ordinal sensitivity model (OR = 0.91, 95% CI [0.82, 1.00], p = 0.052). No reduction in choice-response accuracy or robust slowing of response latency was observed in the post-COVID consequence group. Among previously infected participants, post-COVID consequences were not significantly associated with CTB performance (B = −0.149, 95% CI [−0.311, 0.013], p = 0.071), choice-response accuracy (OR = 0.80, 95% CI [0.60, 1.07], p = 0.126), or response latency (−0.79%, 95% CI [−2.06%, 0.49%], p = 0.224) after adjustment for acute severity, age, and sex; none of these associations remained significant after false discovery rate correction. Acute COVID-19 severity was likewise not significantly associated with the cognitive outcomes. Overall, self-reported post-COVID consequences were associated with, at most, small and outcome-dependent differences in objective cognitive performance in this young university sample. The findings do not support a broad objective cognitive deficit associated with self-reported post-COVID consequences after accounting for acute disease severity and demographic factors.